Ecosystem-based disaster risk reduction can benefit biodiversity conservation in a Japanese agricultural landscape - Kasada, Minoru; Uchida, Kei; Shinohara, Naoto; Yoshida, Takehito (Frontiers in Ecology and Evolution, 2022)
Ecosystem-based disaster risk reduction (Eco-DRR) has attracted increased attention as a sustainable way to achieve both disaster risk reduction and biodiversity conservation, although there have been few quantitative evaluations of the potential impacts of Eco-DRR on biodiversity. Here, we examined the influences of flood hazard and land-use patterns on biodiversity by focusing on the species richness of plants, butterflies and odonates, and the abundance of two frog species in a rural landscape of Wakasa town, Fukui Prefecture, Japan. The direct effect of exposure to flood hazard on the studied taxa was not significant, whereas landscape factors associated with flood hazard significantly influenced either of the taxa in different magnitudes. We then exercised a scenario analysis by replacing urban land-use by non-urban, agricultural land-use (paddy fields in this case) to reduce exposure to flood hazard and projected the impacts on biodiversity. Our results demonstrated that the land-use replacement potentially reduces the risk of flooding by up to 5.19 billion yen (ca. 46 million US$) and, at the same time, positively influences the species richness and abundance, although the ecological impacts are different depending on taxon and spatial location. The land-use replacement was expected to result in the increase of plant richness and abundance of Daruma pond frog at a location by up to 16% and 25%, respectively. On the other hand, butterfly richness at a location was presumed to decrease by until -68%, probably due to their dependence on domestic gardens. The abundance of Japanese wrinkled frog did not show such a clear spatial variation. This study highlights the significance of land-use replacement as an Eco-DRR measure to reduce the disaster risk and conserve biodiversity in the agricultural landscape.